Methods for Testing, Assessment and Analysis of the Security of University Information Systems - Andonov, Venko (Research Papers, 2024)
The methods for testing, evaluating and analyzing the security of university information systems aim to build a unified framework that leads to an increase in information security in this type of institution, which is characterized by the administration of a huge volume of sensitive information of a diverse nature. Security testing is a multifaceted process involving steps to ensure the safety of systems in their entirety. The proposed methods have been tested with three systems of the University of National and World Economy, and one of them is presented here; and conclusions are drawn to increase security and include the described procedures as a permanent practice.
Keywords: Software; Information security; Security testing; Vulnerabilities; Cybersecurity